Implementasi Model Project Based Learning pada Mata Pelajaran PAI untuk Meningkatkan Keterampilan Kolaboratif Peserta Didik di SMA Darussalam Medan - Waliyen Kurnia; Muhammad Yunan Harahap; Charles Rangkuti (Islamic Education, 2026)
This study examines the implementation of Project-Based Learning (PBL) in Islamic Religious Education to strengthen students’ collaborative skills in contemporary classroom learning. Previous studies on PBL in Islamic education have mainly focused on cognitive achievement, while limited attention has been given to the collaborative processes developed during learning activities. This research aims to analyze how PBL contributes to the development of collaboration skills integrated with Islamic educational values. The study employed a qualitative descriptive approach with a case study design conducted at an Islamic junior high school involving 32 eighth-grade students and one Islamic Religious Education teacher. Data were collected through classroom observations, semi-structured interviews, and documentation analysis. The findings reveal that PBL creates a more participatory and student-centered learning environment through group discussions, project planning, task distribution, and presentations. Students demonstrated increased participation, communication, shared responsibility, and confidence during collaborative activities. In addition, Islamic values such as cooperation (ta’awun), honesty, and accountability were reflected in students’ interactions throughout the project process. The study concludes that PBL is not only an instructional strategy but also an effective pedagogical approach for integrating collaborative competence and character education in Islamic Religious Education. This research implies that PBL can support the development of twenty-first century skills while strengthening students’ social and religious character in classroom learning.